El liberalismo a la conquista del amor. Algunas constataciones y reflexiones sobre el consumo sentimental y sexual de masa en la era de internet - Lardellier, Pascal (Revista de Sociología, 2015)
Since ten years, the increase of meeting websites for singles has helped to introduce technology and “industrialize” the emotional-sexual relationships. This paper shows that more widely the principles of liberalism as doctrine have taken over love relationships in a variety of ways, because a new relationship economy, based on effectiveness, interchangeability, performance and profitability, largely prevails over these meeting websites.